THE EFFECT OF JAMU FORMULAS ON BODY WEIGHT, ANTIOXIDANT ACTIVITIES, AND ANTIBODY TITER IN CHICKEN / Pengaruh Jenis Jamu terhadap Bobot Badan, Aktivitas Antioksidan dan Titer Antibodi Ayam - Bagem BR Sembiring; Ening Wiedosari; Sujianto Sujianto (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Medicinal plants are useful to increase body immunity, body weight, appetite, and improve health both for human and animal. The research aimed to obtain functional drink formula for chicken, called jamu, made with spices and medicinal plants. These trials consisted of 3 activities; first, raw materials preparation include fermentation and extraction, second, functional drink formulation in form liquid and powder with pH and IC50 value as parameters, third, efficacy test of formulas that had the strongest antioxidant. The treatments were categorized as group I (chicken were fed with jamu, without vaccination), group II (fed with jamu for two weeks then vaccinated), group III (jamu feeding complemented by vaccination), group IV (control, only vaccination). The third activity was arranged in a randomized block design with 6 replications. Parameters observed were body weight increment and antibody titer. The fermentation time and formula composition showed no significant effect on pH until the third day (4.31 - 4.68), but they indicated significant effect on pH from the fourth day, declined until the seventh day (3.65-4.26). The type and compositions of the formula significantly affected IC50 value. The smallest of IC50 value of liquid and powder formulas were 7796.25 ppm and 244.57 ppm, respectively. The incremental body weight regarding liquid, powder, and control formulas were 365.55 g / week, 351.22 g / week, and 326.66 g / week, respectively. The highest antibody titer was at group III that had 4.50 (log 2), whereas control was 3.30 (log2). The combination feeding, jamu formula and vaccine, was able to increase body weight increment and antibody titer on chicken.Keywords: medicinal plants, functional drink, IC50, broilers, antibody titers AbstrakTanaman obat digunakan untuk meningkatkan daya tahan tubuh, bobot badan, nafsu makan, mencegah penyakit, serta pemulihan kesehatan manusia dan hewan. Penelitian bertujuan mendapatkan formula minuman fungsional untuk ayam berbasis tanaman rempah dan obat. Kegiatan meliputi 3 aktivitas (1) Penanganan bahan baku, fermentasi dan ekstraksi (2) Formulasi minuman fungsional (cair dan serbuk) dengan parameter pH dan nilai IC50. (3) Uji efikasi formula cair dan serbuk yang menghasilkan aktivitas antioksidan terkuat. Perlakuan: kelompok I, ayam hanya diberi formula jamu selama dua minggu, kelompok II, ayam diberi formula jamu selama dua minggu sebelum vaksinasi, kelompok III, ayam divaksin sebelum diberi formula jamu selama dua minggu, kelompok IV, ayam hanya divaksinasi. Kegiatan (3) menggunakan Rancangan Acak Kelompok dengan 6 ulangan dan parameter pengamatan yaitu penambahan bobot badan dan titer antibodi. Waktu fermentasi dan komposisi formula tidak menunjukkan efek yang signifikan pada pH sampai hari ketiga (4,31-4,68), namun signifikan pada hari keempat ditandai dengan penurunan pH sampai hari ketujuh (3,65-4,26). Jenis dan komposisi formula secara signifikan mempengaruhi nilai IC50. Nilai IC50 terkecil dari formula cair adalah 7796,25 ppm dan serbuk 244,57 ppm. Kenaikan berat badan dengan formula jamu cair yaitu 365,55 g / minggu, serbuk 351,22 g / minggu dan kontrol 326,66 g / minggu. Titer antibodi tertinggi adalah 4,50 (log2) yang ditunjukkan oleh kelompok III, sedangkan kontrol 3,30 (log2). Minuman fungsional (jamu) ditambah dengan vaksinasi mampu meningkatkan pertambahan berat badan dan titer antibodi ayam.Kata kunci: Tanaman obat, minuman fungsional, IC50, ayam broiler, titer antibodi